2005
DOI: 10.1093/pan/mpi011
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Conflicting Gauss-Markov Conditions in the Classical Linear Regression Model

Abstract: This article reconciles conflicting accounts of Gauss-Markov conditions, which specify when ordinary least squares (OLS) estimators are also best linear unbiased (BLU) estimators. We show that exogeneity constraints that are commonly assumed in econometric treatments of the Gauss-Markov theorem are unnecessary for OLS estimates of the classical linear regression model to be BLU. We also generalize a set of necessary and sufficient conditions first established by McElroy (1967, Journal of the American Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For multiple regression, data normality or normal distribution of collected data is a vital assumption [17]. Table 4 showed that skewness and kurtosis were between ±1.96 [18], which indicated data normality.…”
Section: Data Normalitymentioning
confidence: 98%
“…For multiple regression, data normality or normal distribution of collected data is a vital assumption [17]. Table 4 showed that skewness and kurtosis were between ±1.96 [18], which indicated data normality.…”
Section: Data Normalitymentioning
confidence: 98%
“… See Shanken (1992) for an approach to correct for standard error bias in asset pricing studies estimating market (and other) betas.10 The treatment and language associated with this and other Gauss-Markov assumptions varies across econometric textbooks (see, e.g., table 1 and the related discussion inLarocca [2005]). …”
mentioning
confidence: 99%